Pengaruh Motivasi Intrinsik Dan Iklim Sekolah Terhadap Kinerja Mengajar Guru SMP Negeri Se-Kabupaten Rejang Lebong - Danim, Sudarwan; Yenni Zulaizah; Putri Kartiwi, Asti (Manajer Pendididikan, 2023)
Teacher performance is an important part of measuring the quality of education in Indonesia. Important factors that play a role in improving teacher performance are intrinsic motivation and organizational climate. This study aimed to analyze the influence of intrinsic motivation and organizational climate on the teaching performance of Rejang Lebong Regency Junior High School teachers. The research is expected to be useful to teachers, principals, and policymakers. The research methods used in this study are the combined method and the quantitative method. The primary data collection technique using questionnaires is teachers. The population used in this study was 786 teachers from Rejang Lebong Regency Junior High School, with a sample of 118 teachers. An analytical technique used to test research hypotheses is to use simultaneous regression with significance testing. The findings suggest that intrinsic motivation and school climate together have a positive and significant impact on the teaching performance of Rejang Lebong Regency Junior High School teachers during the learning process. Advice to teachers, principals, and local offices to continue to contribute to improving the performance of teachers in the Rejang Lebong District Junior High School.